An interview with Anwar Ridhwan: a Malaysian National Laureate - Aziz , Nurul Fateha; Quayum, Mohammad Abdul (IIUM, 2010)
An interview with Anwar Ridhwan that investigates the different aspects and facets of Malaysian literature and culture, especially literature in the Malay language.